Collegiate Athletic Trainers' Confidence in Helping Female Athletes With Eating Disorders - Vaughan, Jennifer L. (National Athletic Trainers' Association, Inc., 2004)
OBJECTIVE: To examine college athletic trainers' confidence in helping female athletes who have eating disorders. DESIGN AND SETTING: We mailed a 4-page, 53-item survey to head certified athletic trainers at all National Collegiate Athletic Association Division IA and IAA institutions (N = 236). A 2- wave mailing design was used to increase response rate. SUBJECTS: A total of 171 athletic trainers returned completed surveys for a response rate of 77%. Eleven institutions either did not identify their head athletic trainer or did not have an identifiable mailing address. Two surveys were undeliverable because of incorrect mailing addresses. MEASUREMENTS: The survey consisted of 4 subscales: (1) efficacy expectation, (2) outcome expectation, (3) outcome value, and (4) experience in dealing with eating disorders. Content validity was established by review from a national panel of experts. Reliability ranged from .66 to .73 for the subscales. RESULTS: Although virtually all athletic trainers (91%) had dealt with a female athlete with an eating disorder, only 1 in 4 (27%) felt confident identifying a female athlete with an eating disorder, and only 1 in 3 (38%) felt confident asking an athlete if she had an eating disorder. One in 4 athletic trainers (25%) worked at an institution that did not have a policy on handling eating disorders. Almost all athletic trainers (93%) felt that increased attention needs to be paid to preventing eating disorders among collegiate female athletes. CONCLUSIONS: Collegiate athletic programs are encouraged to develop and implement eating-disorder policies. Continuing education on the prevention of eating disorders among athletes is also strongly recommended.